2014
DOI: 10.1111/jvs.12195
|View full text |Cite
|
Sign up to set email alerts
|

Fire frequency, agricultural history and the multivariate control of pine savanna understorey plant diversity

Abstract: Question: Human-altered disturbance regimes and agricultural land uses are broadly associated with reduced plant species diversity in terrestrial ecosystems. In this study, we seek to understand how fire frequency and agricultural landuse history influence savanna understorey plant diversity through complex relationships (i.e. indirect effects) among multiple biophysical variables.Location: Fort Bragg, NC, US, Savannah River Site, SC, US and Fort Stewart, GA, US. Methods:We use structural equation modelling (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 75 publications
(163 reference statements)
0
39
0
2
Order By: Relevance
“…In frequently-burned systems, combustion is important for preventing litter accumulation and maintaining plant diversity [49]. We found that fires in triennially-burned sites combusted a greater proportion of P .…”
Section: Discussionmentioning
confidence: 94%
“…In frequently-burned systems, combustion is important for preventing litter accumulation and maintaining plant diversity [49]. We found that fires in triennially-burned sites combusted a greater proportion of P .…”
Section: Discussionmentioning
confidence: 94%
“…This discrepancy between our study and others may have occurred because any establishment limitation slowing re‐assembly in post‐agricultural longleaf pine woodlands were overwhelmed by stronger community assembly constraints occurring uniformly in both community types. In particular, post‐agricultural woodlands and remnant woodlands experienced equally strong fire suppression and consequently support deep litter and duff layers (Brudvig et al ), which suppress species richness in longleaf pine woodlands (Hiers et al , Veldman et al ). Another explanation for differences between these results and others is that our post‐agricultural sites were all immediately adjacent to remnant sites.…”
Section: Discussionmentioning
confidence: 99%
“…The pine species are found over a huge rainfall range of 900 mm , MAP , 3200 mm ( [65]; www.gbif. org, accessed 27 March 2016) and are often associated with low-nutrient soils, similar to pine savannahs in North America [78,79]. This physiognomic similarity may indicate that Asian pine savannahs persist where growth rates are slow due to soil nutrient limitation and fire occurs regularly [79].…”
Section: (C) Pine Savannahsmentioning
confidence: 99%
“…org, accessed 27 March 2016) and are often associated with low-nutrient soils, similar to pine savannahs in North America [78,79]. This physiognomic similarity may indicate that Asian pine savannahs persist where growth rates are slow due to soil nutrient limitation and fire occurs regularly [79]. The herbaceous layer is dominated by fire-adapted Andropogoneae grasses (Cymbopogon, Eulalia, Imperata, Themeda) [61].…”
Section: (C) Pine Savannahsmentioning
confidence: 99%
See 1 more Smart Citation